On teething in infants: encore - V. M. Studenikin (Лечащий Врач)
The article focuses on teething in infants. Some disputable and additional points of this physiological process are discussed. Special attention is attributed to the facilities available for management of pathological symptoms accompanying primary tooth eruption process. Safety items and toxicological quality control of plant-based teething gels for infants are considered.